A Comprehensive Study of Lupin Seed Oils and the Roasting Effect on Their Chemical and Biological Activity - Eman F. Al-Amrousi; Ahmed N. Badr; Adel G. Abdel-Razek; Karolina Gromadzka; Kinga Drzewiecka; Minar M. M. Hassanein (Plants, 2022)
The present investigation aimed to study the impact of roasting on the chemical composition and biological activities of sweet and bitter lupin seed oils. Lupin oils were extracted using petroleum ether (40–60) with ultrasonic assisted method. Lupin Fatty acids, phytosterols, carotenoids, and total phenolic contents were determined. In addition, antioxidant, antimicrobial, and antifungal activities were evaluated. The results showed a ratio between 7.50% to 9.28% of oil content in lupin seed. Unroasted (bitter and sweet) lupin oil contained a high level of oleic acid ω9 (42.65 and 50.87%), followed by linoleic acid ω6 (37.3 and 34.48%) and linolenic acid ω3 (3.35 and 6.58%), respectively. Concerning phytosterols, unroasted (bitter and sweet lupin) seed oil reflected high values (442.59 and 406.18 mg/100 g oil, respectively). Bitter lupin oil contains a high amount of phenolics, although a lower antioxidant potency compared to sweet lupin oil. This phenomenon could be connected with the synergistic effect between phenolics and carotenoids higher in sweet lupin oil. The results reflected a more efficiently bitter lupin oil against anti-toxigenic fungi than sweet lupin oil. The roasting process recorded enhances the antimicrobial activity of bitter and sweet lupin seed oil, which is linked to the increment in bioactive components during the roasting process. These results concluded that lupin oil deems a novel functional ingredient and a valuable dietary fat source. Moreover, lupin oil seemed to have antifungal properties, which recommended its utilization as a carrier for active-antifungal compounds in food products.